Triglycerides glucose index and high-sensitivity C-reactive protein are predictors of outcome in chronic coronary syndrome. (20th July 2021) - Neglia, D; Aimo, A; Caselli, C; Gimelli, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: It is unknown whether insulin resistance (IR) and inflammation identify residual prognostic risk in patients with chronic coronary syndrome (CCS). Aims: To assess whether the triglyceride-glucose (TyG) index and high-sensitivity C-reactive protein (hs-CRP) are independent predictors of outcome in CCS. Methods: TyG index and hs-CRP were evaluated in 1097 consecutive patients (75% men, median age 72 years) with known (26%) or suspected coronary artery disease (CAD) undergoing stress-rest myocardial perfusion scintigraphy (MPS) and coronary angiography and followed-up for a median of 4.5-year. Results: Moderate/severe perfusion abnormalities during stress were documented in 60% of patients, obstructive CAD in 74%, and 36% underwent early revascularization. TyG index was 8.9 (median, interquartile interval 8.6-9.2) and of hs-CRP was 0.3 mg/L (0.1-0.8). Cardiac death or myocardial infarction occurred in 103 patients and all-cause death in 65. Patients in the fourth TyG quartile (TyG ≥ 9.2), with hs-CRP ≥ 2 mg/L or with both had the shortest survival free from cardiac events or all-cause death. TyG predicted cardiac events (HR 2.46, 95% CI 1.59-3.79, p < 0.001) and all-cause death (HR 3.64, 95% CI 2.22-5.96, p < 0.001) independently of other risk factors, perfusion abnormalities or obstructive CAD. Hs-CRP was also an independent predictor of all-cause death (HR 1.11, 95% CI 1.04-1.19, p = 0.002) and reclassified the risk over the other variables and TyG (IDI 0.05, 95% CI 0.01-0.07, p = 0.005). Conclusions: The TyG index identifies a high residual risk of cardiac events in patients with CCS. The TyG index and hs-CRP are strong and interacting predictors of all-cause death.